PENGARUH KOORDINASI PIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR CAMAT ANGGANA KABUPATEN KUTAI KARTANEGARA - Iradat, Fajri (PREDIKSI, 2012)
This Research target is to know what Head of coordination have an effect on to Discipline Work the Officer. The research do in Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara Result of research indicate that the head coordination [of Part of Arranging Effort very having an effect on to officer discipline, in the meaning that discipline factor work the officer at Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara from month to month even from year to year experience of the change mounting. This matter [is] followed also by Head Coordination which in this case function as cause variable. To increase discipline work the officer, beside factor co-ordinate the head, hence factor of[is other;dissimilar require to get the attention so that discipline work the officer at office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara earn remain to be improved